IoT in Agriculture Industry - Ekky Novriza Alam (Jurnal Sistem Cerdas, 2020)
Indonesia is known as an agricultural country that has an agricultural area of 7.1 million hectares in 2018. The agricultural sector is one sector that has great potential to get many benefits by implementing IoT technology. IoT implementation has several obstacles such as hardware, software, communication technology, and security. This paper aims to describe IoT-related studies in the agricultural sector that have been carried out since 2010 in the hope of providing evidence that transforming the traditional agricultural sector into a modern agricultural sector is very possible in Indonesia.